For this was I born : the human conditions in USSR slave labor camps . photographs, testimonies, poems, readings, petitions, letters and other documents - compiled and edited by Yuri R. Shymko. (UCRAINCA Research Institute, 1973)
Includes bibliography: p. [189]-[190]